Materials Processing Fundamentals - Zhang, Lifeng; Allanore, Antoine; Wang, Cong.; Yurko, James; Crapps, Justin; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
This collection provides researchers and industry professionals with complete guidance on the synthesis, analysis, design, monitoring, and control of metals, materials, and metallurgical processes and phenomena. Along with the fundamentals, it covers modeling of diverse phenomena in processes involving iron, steel, non-ferrous metals, and composites. It also goes on to examine second phase particles in metals, novel sensors for hostile-environment materials processes, online sampling and analysis techniques, and models for real-time process control and quality monitoring systems.
Keywords: Metals; Materials -- Analysis; Mechanical engineering; Metals and Alloys; Characterization and Analytical Technique; Mechanical Engineering